2014
DOI: 10.1038/nri3777
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of myeloid cell differentiation, identity and function

Abstract: Myeloid cells are crucial effectors of the innate immune response and important regulators of adaptive immunity. The differentiation and activation of myeloid cells requires the timely regulation of gene expression; this depends on the interplay of a variety of elements, including transcription factors and epigenetic mechanisms. Epigenetic control involves histone modifications and DNA methylation, and is coupled to lineage-specifying transcription factors, upstream signalling pathways and external factors rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
233
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(248 citation statements)
references
References 98 publications
4
233
0
2
Order By: Relevance
“…Furthermore, genetic deficiency of EZH2 increases natural killer (NK) cell lineage commitment and differentiation in vivo [11]. These findings suggest that immune cell differentiation depends on stage-and lineage-specific epigenetic regulators, such as PcG, which determine genome-wide expression patterns in precursors [12,13]. The mixed-lineage leukemia proteins (MLL) are orthologs of TrxG genes that functionally antagonize PcG [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, genetic deficiency of EZH2 increases natural killer (NK) cell lineage commitment and differentiation in vivo [11]. These findings suggest that immune cell differentiation depends on stage-and lineage-specific epigenetic regulators, such as PcG, which determine genome-wide expression patterns in precursors [12,13]. The mixed-lineage leukemia proteins (MLL) are orthologs of TrxG genes that functionally antagonize PcG [8].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Several mechanisms are involved in the development of innate immune memory, among which epigenetic histone modifications (e.g., histone methylation and acetylation), and autophagy play a central role. Monocytes are functionally reprogrammed for either enhanced (training) or decreased (tolerance) cytokine production, depending on the type and concentration of MAMPs they encountered 17,[20][21][22] ( Figure 1). The epigenetic reprogramming of monocytes after MAMP stimulation results in functional as well as morphological changes, including cell surface marker modifications such as upregulation of TLR expression.…”
Section: The Concept Of Trained Immunity: a Novel Type Of Immune Memorymentioning
confidence: 99%
“…While the importance of epigenetic regulation of ETSdependent transcription is well established in hematopoiesis and cancer, 55,[66][67][68] the mechanisms by which ETS activity are modulated at epigenetically modified DNA, with or without nucleosome, are not well understood. Genomic surveys have found that hematopoietic ETS transcription factors are over-represented in hypermethylated regions.…”
Section: Differential Tolerance To Cpg Methylationmentioning
confidence: 99%